PERAN MAHKAMAH KONSTITUSI DALAM PENGUATAN PRINSIP CHECKS AND BALANCES DALAM SISTEM KETATANEGARAAN INDONESIA - Kurniawati, Dian; Rohmah, Elva Imeldatur (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The principle of checks and balances is one of the fundamental elements that plays a role in maintaining the balance of power between the branches of government, namely the executive, legislative, and judicial branches. The Constitutional Court has a role in supervising legislative and executive institutions so that the balance of power and the constitution are maintained in Indonesia. The supervisory function of the Constitutional Court is, reviewing laws against the 1945 Constitution, resolving authority disputes between state institutions, and supervising policies from executive institutions. This research is normative legal research, with statutory, case, and conceptual approaches. Some examples of the supervisory role of the Constitutional Court are the Constitutional Court Decision Number 90/PUU-XVIII/2020, which regulates authority disputes between the President and the Regional Representative Council. In this case, the Constitutional Court emphasized that the Regional Representative Council has more substantial rights in providing considerations on laws related to regional autonomy. Apart from that, Constitutional Court Decision Number 36/PUU-XV/2017 shows how Constitutional Court Decisions can influence the running of state institutions, especially in the legislative and executive context. As well as Constitutional Court Decision Number 70/PUU-XXII/2024, which focuses on the age requirements for regional head candidates. Through these decisions, the Constitutional Court not only monitors and balances power between state institutions but also protects the constitutional rights of citizens and ensures that government processes are in accordance with democratic principles and the supremacy of law. Abstrak Prinsip checks and balances merupakan salah satu elemen fundamental yang berperan menjaga keseimbangan kekuasaan antara cabang-cabang pemerintahan, yakni eksekutif, legislatif, dan yudikatif. Mahkamah Konstitusi memiliki peran dalam pengawasan lembaga legislatif dan eksekutif sehingga terjaga keseimbangan kekuasaan dan konstitusi di Indonesia. Fungsi pengawasan dari Mahkamah Konstitusi yaitu, pengujian undang-undang kepada Undang-Undang Dasar 1945, penyelesaian sengketa kewenangan antar lembaga negara, serta menjadi pengawasan kebijakan dari lembaga eksekutif. Penelitian ini merupakan penelitian hukum normatif, dengan pendekatan perundang-undangan, kasus, dan konseptual. Beberapa contoh peran pengawasan Mahkamah Konstitusi adalah hadirnya Putusan Mahkamah Konstitusi Nomor 90/PUU-XVIII/2020 yang mengatur sengketa kewenangan antara Presiden dan Dewan Perwakilan Daerah. Dalam kasus ini, Mahkamah Konstitusi menegaskan bahwa Dewan Perwakilan Daerah memiliki hak yang lebih substansial dalam memberikan pertimbangan terhadap undang-undang terkait otonomi daerah. Selain itu, Putusan Mahkamah Konstitusi Nomor 36/PUU-XV/2017 yang menunjukkan bagaimana Putusan Mahkamah Konstitusi dapat memengaruhi jalannya kelembagaan negara, terutama dalam konteks legislatif dan eksekutif. Serta Putusan Mahkamah Konstitusi Nomor 70/PUU-XXII/2024, yang berfokus pada syarat usia calon kepala daerah. Melalui putusan-putusan tersebut, MK tidak hanya mengawasi dan menyeimbangkan kekuasaan antar lembaga negara, tetapi juga melindungi hak-hak konstitusional warga negara dan memastikan proses pemerintahan yang sesuai dengan prinsip demokrasi dan supremasi hukum.